METODE INTERAKSI PARENTING: UPAYA MENGOPTIMALKAN PENDIDIKAN SISWA SEJAK DINI - Moh Rifai (Universitas PGRI Madiun, 2013)
Parents are obliged to take care of their children’s future, especially by rendering sufficient education. Children are believed to bring about happiness every now and then, who generate family’s pride up to the almighty judication. Some people are save and some are not in that court, where children will give sigificant contribution in it. That’s why the children’s well being has become the parents obligation. To bring about children’s well being, parents should also render the good treatments during the life cycle of their children. The main duties of parents for their children are giving them the good names, sending them to the good schools where they can learn religion, and marry them to their good spouses. Psychologically, when children are sent to school for the first time, they will feel that they are put apart from parents’ care, so that may of them have to go difficult phase of adjustment. The adjustment includes that of education so as to run as naturally as possible. To get the naturality of the education delegation, teachers and educators are obliged to be able to nurture any value to students as naturally as possible. Parenting model of teaching serves the requirements of teaching children just the way the parrents do, so that it is assumptively effective in teaching elementary students by taking consideration on the psychologial aspect of children. Key words: Parenting Model of teaching, children education optimalization